Screening and Validation of p38 MAPK Involved in Ovarian Development of Brachymystax lenok - Huang, Tianqing; Gu, Wei; Liu, Enhui; Zhang, Lanlan; Dong, Fulin; He, Xianchen; Jiao, Wenlong; Li, Chunyu; Wang, Bingqian; Xu, Gefeng (Frontiers in Veterinary Science, 2022)
Brachymystax lenok (lenok) is a rare cold-water fish, native to China, which has high meat quality; its wild population has declined sharply in recent years. It is therefore necessary to explore the molecular mechanisms underlying the development and reproduction of lenoks for artificial breeding and genetic improvement. The lenok comparative transcriptome was analysed by combining single molecule, real-time and next generation sequencing (NGS) technology; differentially expressed genes (DEGs) were identified in five tissues (head kidney, spleen, liver, muscle, and gonad) between immature (300 days post hatching, dph) and mature (3 years post-hatching) lenoks. In total, 234,124 and 229,008 full-length non-chimeric reads were obtained from immature and mature sequencing data, respectively. After NGS correction, 61,405 and 59,372 non-redundant transcripts were obtained for expression level and pathway enrichment analyses. Compared with the mature group, 719 genes with significantly increased expression and 1,727 genes with significantly decreased expression in all five tissues were found in the immature group. Furthermore, DEGs and pathways involved in the endocrine system and gonadal development were identified, and p38 MAPK was identified as potentially regulating gonadal development in the lenok. Inhibiting the activity of p38 MAPK resulted in abnormal levels of gonadotropin-releasing hormone, follicle-stimulating hormone, and estradiol, and affected follicular development. The full-length transcriptome data obtained in this study may provide a valuable reference for the study of gene function, gene expression, and evolutionary relationships in Brachymystax lenok, and may illustrate the basic regulatory mechanism of ovarian development in teleosts.